THE EVALUATION OF METAMIZOLE USE IN SOME PLACES OF PHARMACY SERVICE IN CILACAP COUNTY - Marina Kurniawati; Zullies Ikawati; Budi Raharjo (Faculty of Pharmacy, Universitas Gadjah Mada)
Metamizole is an analgesic antipyretic drug. However, its use has been associated with risk of involving agranulocytosis and aplastic anemia. These reactions are rare and unpredictable. The use of metamizole is controversial, as reflected in the very different regulations among nation affecting it. The study aimed to evaluate the use of metamizole to 406 subjects in some pharmacies in Cilacap County, during December 2009 – February 2010. Methods used in this study questionnaires and interviewing. This conclusions are metamizole was used in female (53.2%) than in male (46.8%); combination of metamizole was used more (77%) than single (23%); metamizol use by purchasing more non-prescription (65.24% ) than by prescription (32.76%). The most common reasons for using metamizole were for headache (70.44%), toothache, analgesic and stomachache. Side effect and drug interaction were not confirmed happen to the subjects. Physical examinations and laboratory results of the 2 subjects among of them showed symptoms of anemia, but the effect which lead to agranulocytosis still need further examination.Key words : metamizole, side effect, drug interaction